Cytotoxic effect and mechanism inducing cell death of α-mangostin liposomes in various human carcinoma and normal cells - Ruthairat Benjakul (2018)
Copyright © 2015 Wolters Kluwer Health, Inc. All rights reserved. The aims of this study were to develop α-mangostin liposomes as well as to evaluate their physicochemical properties and cytotoxic activity. α-Mangostin liposomes were prepared using the reverse-phase evaporation method with lipid composition of phosphatidylcholine to cholesterol at 7: 3 molar ratios; their physicochemical properties and antiproliferative activity were assessed using an MTT assay in four human carcinoma cells [that is, human lung epithelial carcinoma (Calu-3), human colon carcinoma (HT-29), human breast carcinoma (MCF-7), and human colon carcinoma (Caco-2) cells], and two human normal cells [that is, human dermal fibroblasts (HDF) and human adult low-calcium elevated temperature (HaCaT) keratinocytes]. Determinations of morphological changes and oligonucleosomal DNA fragments were also carried out. The liposomal dispersions obtained were unilamellar vesicles as confirmed by cryotransmission and freeze-fracture electron microscopy with a particle size of 114 nm and a ζ potential of -2.56 mV. The 31P-NMR spectra showed that α-mangostin molecules orientated in the phospholipid bilayer membrane. The α-mangostin could appreciably be entrapped with an efficiency and loading of 81 and 4%, respectively. The antiproliferative activity of α-mangostin liposomes in various cancer and normal cells showed a dose-dependent inhibition in all treated cell lines. The antiproliferative effect of α-mangostin liposomes was found to be associated with apoptosis, with differences in sensitivity among the cell lines treated.